Assessing student readiness for Kurikulum Merdeka implementation - Nita Bonita; Susilawati S (Concept : Community Concern for English Pedagogy and Teaching, 2024)
This study assesses students' preparedness for the Kurikulum Merdeka and its implementation. The subject and object of the research were 10th-grade pharmacy students at one of the vocational schools in Cirebon, totalling 19 students. There were sixteen female students and three male students. This research used descriptive-qualitative design. The researchers used questionnaires, interviews, and observations as the instruments. The result of this research indicates that student readiness is so important that students are ready to learn. Moreover, the curriculum must be implemented in all schools by 2024 according to the Ministry of Education and Culture's policy. Nevertheless, the results of this research show that students' readiness to face the Kurikulum Merdeka cannot be considered sufficient as their readiness for this curriculum stands at only 78.7%. Keywords: Student readiness; Kurikulum Merdeka; Implementation